Factorial Design 2n in Bauxite Tailings Flocculation and Bingham Model for Rheological Characteristics - de Araujo, AC; Valadão, GES; Falcucci, A (Paste 2009: Twelfth International Seminar on Paste and Thickened Tailings, 2009)
In the last years, the disposal of tailings in the form of pastes and/or high-density slurries has gained importance as it may present significant advantages in comparison to more traditional disposal techniques. The knowledge of physical chemical characteristics of the material to be disposed, as well as the interactions that result from the use of polymeric flocculants on solid/liquid separation can lead to the formation of pastes and/or high-density slurries with adequate conditions for handling and final disposal. With the help of factorial design tool (2²), with pH and flocculant dosage as independent variables, the effects of three different polyacrylamide flocculants was evaluated on the final per cent solids of a bauxite tailings flocculated material, over a pH range from 5 to 7 and different dosages of flocculants. These factors were analysed by fitting the experimental data to a polynomial model, which plots settling rates response in the form of contour maps. Regarding the final percentage of solids of the flocculated material, a cationic polymer presented the best results among the three flocculants tested. With a dosage of 130 g/t and pH 5, the final percentage of solids (by wt.) was 31.2% after one hour. The rheological characteristics for different percentage of solids are determined with the help of the Bingham model, where the viscosity and yield stress of a bauxite tailing are available without a presence of flocculant. According to the utilised model, the yield stress show a signification increase for to the slurry with 25–30 per cent of solid by weight, with a viscosity of between 8.2 and 13.0 cP and a yield stress between 3.0 and 6.8 Pa.